KOLOKASI BERKONTRUKSI œNOMINA + VERBA DALAM BAHASA JEPANG PADA MINNA NO NIHONGO SHOKYUU DAN NIHONGO CHUUKYUU - Amalia Rizqi Khoiriyah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2018)
This research is motivated by the existence of problems in language, because each language has their own habits to join the words with certain words. This habit is called collocation. The focuss in this study, is the use of collocation with the construction of "Nomina + Verba" and its role in Japanese in Minna no Nihongo Shokyuu and Nihongo Chuukyuu. Collocation with verb types is considered as the focus in this study, because verbs are 'lives' in a sentence. The results of this study indicate that the construction of nouns + verbs on Nihongo Shokyuu and Nihongo Chuukyuu are 4 constructions: (a) Noun + wo + Verba there are 3 roles of syntax, namely Objective, Locative and role of Time, (b) Noun + ni + Verb role found are Objective, Locative, Time, Opposition, Direction, Giver, Receiver and Results role roles, c) Noun + ga + role verbs which are objective-patient roles. This is because the construction that meets Nomina + Verba requirements is only in the patient role. Then the last one is construction (d) Nominal + de + Verba with 4 synthetic roles, Locatives role, Time, Instrument and cause / reason. The type of collocation studied is limited collocation, fixed collocation and idiom.